INTERNALISASI PENDIDIKAN KARAKTER DALAM PERSPEKTIF DAYAH - Helmi (FITRAH: International Islamic Education Journal, 2021)
Dayah as the oldest education world in Aceh is also the world trying to educate his students (santri) not only able to master the science of religion (transfer of knowledge) also focuses the students are able to interrogate themselves figure character and character karimah. In general, education not only makes children smart, but also must be able to create noble values or character. Education maqasid character (purpose), first, develop the potential of the heart or conscience of learners as human beings and citizens who have the character of the nation. Second, develop the commendable habits and behaviors of learners and in line with the universal values and cultural traditions of a religious nation. Third, Instill the spirit of leadership and responsibility of learners as the successor of the nation. Fourth, Develop the ability of learners to become independent, creative, and national-minded human beings. Dayah Aceh in the internalization of character education does it by several methods, including: method of accuracy, method of practice and habituation, method of advising, method of targhib wa tahzib (motivation and punishment), method of persuasion, method of story in addition to the methods mentioned above there are other methods, among others, methods of proverbs (examples), tajribi (practice experience) and others. At least with the existence of a berkarkater education in dayah able to restore ilÄhiyyah values in humans (fisÄn kÄmil) especially santri with the guidance of the Qur'an and al-HadÄ«th, ijma' and qias so that it becomes a human being with noble character (insÄn kÄmil) through the touch of the teacher's hand in dayah.